Diversities of disability caused by lung cancer in the 66 Belt and Road initiative countries: a secondary analysis from the Global Burden of Disease Study 2019 - Zhu, Zhenfeng; Ye, Wenjing; Zhang, Li; Jia, Wenchang; Chen, Binghong; Wang, Qizhe; Cheng, Xuelin; Yang, Shijia; Zhang, Zhaoyu; Ding, Yibo; Li, Xiaopan (Frontiers in Oncology, 2023)
Objectives: Due to the increase in life expectancy and the aging of the global population, the "Belt and Road" ("B&R") countries are faced with varying degrees of lung cancer threat. The purpose of this study is to analyze the differences in the burden and trend of lung cancer disability in the "B&R" countries from 1990 to 2019, so as to provide an analytical strategy basis to build a healthy "B&R".Methods: Data were derived from Global Burden of Disease 2019 (GBD 2019). Incidence mortality, prevanlence, the years lived with disability (YLDs) and disability-adjusted life-years (DALYs) of lung cancer and those attributable to different risk factors were measured from 1990 to 2019. Trends of disease burden were estimated by using the average annual percent change (AAPC) and the 95% uncertainty interval (UI) were reported.Results: China, India and Russian Federation were the three countries with the highest burden of lung cancer in 2019. From 1990 to 2019, the AAPC of incidence, prevanlence, mortality and DALYs generally showed a downward trend in Central Asia (except Georgia) and Eastern Europe, while in China, South Asia (except Bangladesh), most countries in North Africa and the Middle East, the trend was mainly upward. The AAPC of age-standardized incidence, 1.33% (1.15%-1.50%), 2.prevanlence, mortality and DALYs from lung cancer in China increased by 24% (2.10%-2.38%), 0.94% (0.74%-1.14%) and 0.42% (0.25%-0.59%) respectively. A downward trend of the AAPC values of age-standardized YLDs rate in male was shown in the vast majority of "B&R" countries, but for females, most countries had an upward trend. For ≥ 75 years adults, the age-standardized YLDs rate showed an increasing trend in most of the "B&R" countries. Except for DALYs rate of lung cancer attributable to metabolic risks, a downward trend of DALYs rate attributable to all risk factors,behavioral risks and environmental/occupational risks were shown in the vast majority of "B&R" countries.The burden of lung cancer in "B&R" countries varied significantly between regions, genders and risk factors. Strengthening health cooperation among the 'B&R' countries will help to jointly build a community with a shared future for mankind.